1996
DOI: 10.1007/s002130050095
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and neurochemical differences between acute and tardive vacuous chewing movements induced by haloperidol

Abstract: Late onset vacuous chewing movements (VCMs) from chronic neuroleptic treatment have been used as a rat model of tardive dyskinesia (TD). Early onset VCMs have also been observed, raising questions about the validity of this model. To assess the relationship between these two types of VCMs, pharmacological and neurochemical properties of early and late onset VCMs were compared. "Acute" VCMs were induced by daily intraperitoneal injections for 1-21 days. "Tardive" VCMs were induced by intramuscular injections of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 60 publications
1
36
2
Order By: Relevance
“…An issue that could be raised regarding this study is the shorter (8 weeks) duration of treatment compared to other VCM investigations that have been longer than 6 months (eg Egan et al, 1996). While our study was limited to 8 weeks, the decision to reduce the length of the study was based on the finding that the VCM behavior plateaus beyond 5 weeks of treatment in this study and in other VCM experiments conducted in our laboratory (Turrone et al, 2002(Turrone et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An issue that could be raised regarding this study is the shorter (8 weeks) duration of treatment compared to other VCM investigations that have been longer than 6 months (eg Egan et al, 1996). While our study was limited to 8 weeks, the decision to reduce the length of the study was based on the finding that the VCM behavior plateaus beyond 5 weeks of treatment in this study and in other VCM experiments conducted in our laboratory (Turrone et al, 2002(Turrone et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, the evidence in support of these hypotheses is largely derived from studies where animals were treated with APs over a brief time period (o21 days) (see Turrone et al, 2002). There is some evidence that early-appearing VCMs may be more neurochemically and pharmacologically related to acute EPS than TD (Egan et al, 1996). Moreover, evidence derived from a recent long-term VCM study has demonstrated that it is not the anticholinergic challenge that reduces VCMs, but some aspect inherent to the injection procedure itself (Sakai et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16][17] Tests that predict the side effects of antipsychotic drugs As mentioned in the introduction, the short-term side effects of first-generation antipsychotic drugs include parkinsonian syndrome, dystonia and akathisia, whereas chronic treatment leads to tardive dyskinesia, which comprises abnormal, excessive, and involuntary movements. 51 Despite a large number of investigations, the mechanisms through which these effects occur remain to be elucidated. These include dopaminergic supersensitivity, excitotoxicity, free radical formation, and a decrease in dopamine transporter density.…”
Section: Disruption Of the Prepulse Inhibition Of The Startle Responsementioning
confidence: 99%